2019
DOI: 10.1155/2019/8571297
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Existing Defects on Mechanical Properties of NC Lining

Abstract: The mechanical properties of the lining are directly affected by defects such as voids behind the lining and insufficient thickness of the lining. In order to quantitatively evaluate this effect, the mechanical behavior of the lining under the influence of the void behind the lining, the insufficient thickness of the lining, and the combination of the two kinds of defects are adopted by the 1/5 scale model test. Based on the experimental research, numerical calculation models based on the CDP model for defect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…According to Figure 6, it can see that with the increase of the displacement, the hysteretic curve of the specimen tends to be full and the energy consumption increases gradually. The energy dissipation capacity of the specimens under high axial compression ratio is relatively large, whether it is the connecting steel or the connecting steel plate in the prefabricated shear wall structure [22][23][24].…”
Section: Structural Systemmentioning
confidence: 99%
“…According to Figure 6, it can see that with the increase of the displacement, the hysteretic curve of the specimen tends to be full and the energy consumption increases gradually. The energy dissipation capacity of the specimens under high axial compression ratio is relatively large, whether it is the connecting steel or the connecting steel plate in the prefabricated shear wall structure [22][23][24].…”
Section: Structural Systemmentioning
confidence: 99%
“…The results showed that the stress state of the lining changed from an axial thrust to a bending moment due to the existence of the void. Zhang et al [ 17 ] considered the voids caused by insufficient thicknesses and established a numerical model for strengthening the lining based on a CDP model. By analyzing the influence of void location, void type, and degree on the mechanical properties of the lining, the results showed that the stiffness of the hollow lining had a weakening effect.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the void significantly reduced the bearing capacity of the lining, as well as increased the local deformation, and significant lining cracking showed at the void location. Zhang et al [ 20 ] verified the effect of voids on lining in Ding’s test [ 19 ] by building a numerical model of CDP. The results showed that the bearing capacity of the lining decreased in an ‘s’-shaped curve with the increase in void.…”
Section: Introductionmentioning
confidence: 99%